Analisis Efisiensi dan Saluran Pemasaran Bawang Daun di Desa Duriaasi Kecamatan Wonggeduku Kabupaten Konawe - Imayanti Imayanti; I Made Sukratman; Leni Saleh (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
The aim of this research is to identify the marketing channel pattern for spring onions in Duriaasi Village, Wonggeduku District, Konawe Regency and analyze the level of marketing efficiency of spring onions in Duriaasi Village, Wonggeduku District, Konawe Regency. The research was carried out from April to June 2024, in Duriaasi Village, Wongeduku District, Konawe Regency. Determining the population was selected from farmers by census, namely all farmers who are trying to grow leeks in Duriaasi Village, Wonggeduku District, Konawe Regency and marketing institutions, namely the number of farmers is 14 people and 3 village collecting traders and 10 retail traders. The analysis used is marketing margin analysis and marketing efficiency.Based on the research results, there are two types of marketing channels for green onions, namely producers to collectors to retailers to consumers who have marketing costs of IDR 1,700/Kg, marketing channel II namely from producers to retailers to consumers which has marketing costs of IDR 1,000/ Kg and the marketing efficiency of green onions in marketing channel I reaches 82% and marketing channel II reaches 70 %. This means that the large percentage share of the price received by farmers and the low marketing costs incurred at leek marketing institutions in Duriaasi Village, Wongeduku District, Konawe Regency.